2021
DOI: 10.1590/2175-3369.013.e20200001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the freedom to build: Long-term outcomes of Elemental’s incremental housing in Quinta Monroy

Abstract: In 2003, the Chilean architecture firm Elemental began to revisit the idea of partially completed housing harnessing the productive capacities of the informal process within a more formal framework. The Quinta Monroy project in the northern Chilean city of Iquique was the first such project and involved the in-situ replacement of an informal settlement. The desire of residents was for a middle-class house that was beyond the scope of their budget or the subsidy. The Elemental project at Quinta Monroy comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…This study focuses mainly on the analysis of the Micro or housing level. Previous studies about incremental housing in Chile Mora et al, 2020;O'Brien et al, 2020;Carrasco & O'Brien, 2021) observed complex social relationships that requires further analysis which is beyond the scope of this study and should be covered in a future research project.…”
Section: Scope and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses mainly on the analysis of the Micro or housing level. Previous studies about incremental housing in Chile Mora et al, 2020;O'Brien et al, 2020;Carrasco & O'Brien, 2021) observed complex social relationships that requires further analysis which is beyond the scope of this study and should be covered in a future research project.…”
Section: Scope and Limitations Of The Studymentioning
confidence: 99%
“…Settlement management and inclusive governance remains a challenge beyond the globally recognized housing designs which balance individual and collective incremental development. Longterm outcomes from sites and services projects and studies about the first Elemental's housing project 'Quinta Monroy' (Millones S., 2017;Carrasco & O'Brien, 2021)…”
Section: Reasons For Housing Adaptationmentioning
confidence: 99%
“…Sobressai-se o objetivo de promover a interação da comunidade e manter as afinidades dos vizinhos. O projeto começou em 2003 e os moradores receberem suas casas em 2005 [15]. Fonte: [13] A Figura 3 mostra o resultado das obras de ampliação construídas após entrega dos embriões.…”
Section: Entac2022 -Ambiente Construído: Resiliente E Sustentávelunclassified
“…Mais de uma década após sua inauguração, grande parte das famílias originais seguem habitando a Quinta Monroy, adicionando e subtraindo partes. Sabemos que há sim, um conjunto de críticas consistentes a este projeto, conforme apontam Carrasco & O'Brien (2021), mas nos parece que, além de fazer coro com as qualidades que dali podemos extrair, as críticas ainda são feitas, em grande medida, atreladas a valores externos à comunidade em questão: valores e diretrizes da academia, do saber legitimado da expertise técnica, considerados centrais e, consequentemente, legítimos.…”
Section: Projeto Como Ação: Práxis Periféricas Não Modelaresunclassified